Value of dynamic and DWI MRI in evaluation of HCC viability after TACE via LI-RADS v2018 diagnostic algorithm - Tamer Yousef Saleh; Suzan Bahig; Naglaa Shebrya; Aya Yassin Ahmed (The Egyptian Journal of Radiology and Nuclear Medicine, 2019)
Abstract Background Detection of the value of DCE (dynamic contrast enhanced) MRI and DWI (diffusion-weighted imaging) in follow-up of treatment response for HCC (hepatocellular carcinoma) lesions post TACE (trans-arterial chemo-embolization) through LI-RADS v2018 algorithmic approach. Results A prospective study was performed on 30 patients with 41 treated hepatic focal lesions. The patients underwent DCE MRI with DWI in less than 1-month duration following TACE procedure and were radiologically assessed to observe tumoral post treatment response; then, another follow-up after another 3 months later was done for non-viable, equivocal, and non-evaluable post treatment response categories. Statistical analysis showed that DCE MRI had 100% level of sensitivity, specificity of 95.24%, PPV of 95.00%, and NPV of 100% with an overall agreement of 97.50%. While on the other hand, statistics showed that DWI has 52.63% level of sensitivity, specificity of 90.48%, PPV of 83.33%, PPV of 67.86%, and NPV of 72.50%. The difference between non-viable and viable groups’ ADC variables was found statistically significant at P value < 0.001, and best cut off value that augments sensitivity and specificity is 1.35. At this ADC value, sensitivity reaches 78.9% and specificity is 85.7%. Conclusions Our study showed that DCE MRI has 100% level of sensitivity via application of LI-RADS v2018 diagnostic algorithmic approach while DWI alone has 52.63% level of sensitivity, yet it can enhance the diagnostic confidence of DCE MRI for post treatment response viability detection.